2019
DOI: 10.1111/jch.13772
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement of ambulatory blood pressure monitoring in the US commercial insurance marketplace

Abstract: Ambulatory blood pressure monitoring (ABPM) is increasingly recommended for confirming hypertension diagnosis and ongoing hypertension monitoring. However, reimbursement in the United States is variable and low compared with other advanced health care systems. We examined the reimbursement of ABPM and factors associated with successful reimbursement. A retrospective analysis of IBM MarketScan® commercial claims database was conducted for patients ≥18 years with ≥1 ABPM claim from January 2012 to December 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Secondly, reimbursement rates are often perceived as insufficient to justify the cost of performing ABPM routinely. Our prior research suggests that median reimbursement rates for ABPM range from approximately $86 to $96, depending on commercial plan type, although nearly 20% of submitted ABPM claims are not reimbursed at all [ 10 ]. Relatedly, patients often incur out-of-pocket expenses for ABPM, which may be cost-prohibitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, reimbursement rates are often perceived as insufficient to justify the cost of performing ABPM routinely. Our prior research suggests that median reimbursement rates for ABPM range from approximately $86 to $96, depending on commercial plan type, although nearly 20% of submitted ABPM claims are not reimbursed at all [ 10 ]. Relatedly, patients often incur out-of-pocket expenses for ABPM, which may be cost-prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of ABPM use is likely more indicative of well-known inequities in prevalence and control of cardiovascular risk factors, including hypertension, in this “stroke belt” region [ 12 ]. Interestingly, our prior work found that claims from the Southeastern U.S. are less likely to be reimbursed than claims from the Northeast [ 10 ]. Taken together, these data suggest a greater need for ABPM in this region, as indicated by the number of claims filed, but lower likelihood of successful reimbursement in the most racially and socioeconomically diverse region in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we previously showed that ABPM claim submissions decreased from 2008 to 2017 and fewer than 0.5% of commercially insured patients with hypertension have had ABPM claims billed to their commercial insurance. 4,7 We hypothesized that one possible explanation for these findings could be low patient acceptance, either because ABPM is cumbersome or because of OPP burden. Our present findings suggest the latter may not be the primary barrier for most individuals with coverage, particularly when excluding deductibles from OPP calculation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Among commercial insurers in the United States, the median reimbursement to providers for each ABPM episode is $89. 7 However, to date, out-of-pocket payment (OPP) for ABPM in the commercial insurance marketplace has not been studied. Given that high OPP may be a significant barrier to patient acceptance of ABPM, we sought to characterize ABPM OPPs in a nationally representative US cohort of patients with commercial insurance.…”
mentioning
confidence: 99%
“…In the US, ABPM testing is reimbursed by Medicare, a national health insurance program covering approximately 55 million Americans. In an analysis of 1970 Medicare beneficiaries, for whom white coat hypertension was the chief indication for reimbursement, the median reimbursement rate was $52 USD (range $33-65) [19] . To qualify, documentation of masked or white coat hypertension using office and home BP measurements is required, and these additional bureaucratic requirements likely further constrain use.…”
Section: Barriers and Disincentives To The Use Of Abpmmentioning
confidence: 99%